A post-transcriptional program coordinated by CSDE1 prevents intrinsic neural differentiation of human embryonic stem cells - Lee, Hyun Ju; Dieterich, Christoph (Nature Communications, 2017)
Unlike transcriptional regulation of hESC identity, little is known post-transcriptionally. Here, the authors show that the RNA binding protein CSDE1 regulates core components of hESC identity, neurectoderm commitment and neurogenesis to maintain pluripotency and prevent neural differentiation.
Gesehen am 02.05.2018